Clinical and Immunological Manifestations of Patients Presenting With Systemic Lupus Erythematosus At Tertiary Care Hospital, Karachi - Ahmed, Asfa; Sultan, Muhammad Omer; Khan, Muhammad Inam; Ahmed, Alisha (Biological and Clinical Sciences Research Journal, 2025)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease that affects multiple organ systems, with a high prevalence among young women. It presents various clinical and immunological manifestations, including arthritis, skin rashes, oral ulcers, hematological abnormalities, and neurological involvement. Early diagnosis and management depend on recognising key clinical symptoms and autoantibody profiles. Understanding SLE patterns in different populations is essential for improving diagnostic accuracy, treatment strategies, and patient outcomes. Objective: This study aims to assess the clinical and immunological characteristics of SLE patients in a tertiary care hospital, identifying common symptoms, disease manifestations, and associated autoantibodies. Methodology: A cross-sectional study was conducted on 131 patients diagnosed with SLE at a tertiary care hospital. Data were collected on demographics, clinical symptoms, and immunological markers, including antinuclear antibodies (ANA), anti-dsDNA, anti-Sm, anti-Ro, anti-La, and antiphospholipid antibodies. Statistical analysis was performed using SPSS version 23 to determine the prevalence and associations of disease manifestations. Results: The study population had a strong female predominance (77.9%), with most patients aged 20–40 (77.9%). Arthritis (67.2%), skin rash (67.2%), oral ulcers (77.1%), and photosensitivity (67.2%) were the most frequent symptoms. Neurological involvement was noted in 36% of patients, while hematological abnormalities included hemolytic anemia (31.3%), thrombocytopenia (29.8%), and leukopenia (13%). Immunological analysis showed ANA positivity in 78.6% of patients, with anti-dsDNA (61.1%) as the most common specific autoantibody. Other antibodies included anti-Sm (20.6%), anti-Ro (15.3%), anti-La (14.5%), and anti-RNP (10.7%). Antiphospholipid antibodies were present in 15.3%–13.7% of patients, indicating a risk of thrombotic complications. Comorbid conditions, such as hypertension (32.8%), diabetes (21.4%), dyslipidemia (16.8%), smoking (25.2%), and obesity (23.7%), were also prevalent, highlighting increased cardiovascular risk. Conclusion: The findings emphasise arthritis, skin rash, oral ulcers, and anti-dsDNA positivity as key features of SLE diagnosis. The high prevalence of autoantibodies and cardiovascular risk factors calls for regular monitoring, multidisciplinary management, and early intervention to improve patient outcomes. Future research should focus on long-term disease progression and genetic predisposition, with more extensive multicenter studies to refine diagnostic and treatment strategies.